The complete mtDNA sequence of the griffon vulture (Gyps fulvus): Phylogenetic analysis and haplotype frequency variations after restocking in the Sardinian population. (October 2017) - Mereu, Paolo; Satta, Valentina; Frongia, Gian N.; Berlinguer, Fiammetta; Muzzeddu, Marco; Campus, Alfonso; Decandia, Luca; Pirastru, Monica; Manca, Laura; Naitana, Salvatore; Leoni, Giovanni G.
Abstract: In Italy the Eurasian griffon Gyps fulvus became extinct between the 19th and 20th centuries, with the exception of Sardinia where is now considered "critically endangered". Here we provide the first whole mitogenome sequence of Gyps fulvus, which was 17, 961 bp long. Evolutionary analysis pointed out a divergence between griffon and black vulture ( Aegypius monachus ) which occurred about 25.8 MYA, while the rise of the Gyps ancestor was dated back at around 5.4 MYA. In addition, the early radiation within the G . fulvus species started between 310 and 120 MYA. To prevent extinction of the Sardinian population, two restocking events were carried out, unfortunately without contributions of genetic evidences. To estimate the impact derived by the restocking activities, mitochondrial D-loop sequences from 22 museum individuals, which died before reintroduction events, were compared with 44 sequences from the extant population. Within the extant samples we detected three haplotypes (Hpt A, B and C). Hpt C showed the lowest frequency and it was not present among the museum samples, while Hpt A and B were found to be the most represented in extant and museum samples, respectively. In order to prevent the loss of genetic variability within the Sardinian population we recommend to refer to the new genetic information provided in the present study before the implementation of recovery programs in the future. Graphical abstract: Highlights: The sequence of the entire mitogenome of Gyps fulvus has been provided. Phylogeny of Gyps fulvus was inferred using mtDNA data. Three mitochondrial haplotypes have been described in Sardinian griffon vulture. Reintroduction actions altered genetics of Sardinian griffon vulture population.